Prognosis after surgical replacement with a bioprosthetic aortic valve in patients with severe symptomatic aortic stenosis: systematic review of observational studies - Foroutan, Farid (BMJ, 2016)
Objective To determine the frequency of survival, stroke, atrial fibrillation, structural valve deterioration, and length of hospital stay after surgical replacement of an aortic valve (SAVR) with a bioprosthetic valve in patients with severe symptomatic aortic stenosis. Design Systematic review and meta-analysis of observational studies. Data sources Medline, Embase, PubMed (non-Medline records only), Cochrane Database of Systematic Reviews, and Cochrane CENTRAL from 2002 to June 2016. Study selection Eligible observational studies followed patients after SAVR with a bioprosthetic valve for at least two years. Methods Reviewers, independently and in duplicate, evaluated study eligibility, extracted data, and assessed risk of bias for patient important outcomes. We used the GRADE system to quantify absolute effects and quality of evidence. Published survival curves provided data for survival and freedom from structural valve deterioration, and random effect models provided the framework for estimates of pooled incidence rates of stroke, atrial fibrillation, and length of hospital stay. Results In patients undergoing SAVR with a bioprosthetic valve, median survival was 16 years in those aged 65 or less, 12 years in those aged 65 to 75, seven years in those aged 75 to 85, and six years in those aged more than 85. The incidence rate of stroke was 0.25 per 100 patient years (95% confidence interval 0.06 to 0.54) and atrial fibrillation 2.90 per 100 patient years (1.78 to 4.79). Post-SAVR, freedom from structural valve deterioration was 94.0% at 10 years, 81.7% at 15 years, and 52% at 20 years, and mean length of hospital stay was 12 days (95% confidence interval 9 to 15). Conclusion Patients with severe symptomatic aortic stenosis undergoing SAVR with a bioprosthetic valve can expect only slightly lower survival than those without aortic stenosis, and a low incidence of stroke and, up to 10 years, of structural valve deterioration. The rate of deterioration increases rapidly after 10 years, and particularly after 15 years.